2017
DOI: 10.18632/oncotarget.15866
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-derived mesenchymal stem cells promote osteosarcoma proliferation and metastasis by activating the STAT3 pathway

Abstract: Osteosarcoma is the most common primary bone malignancy in children and young adults, but the role of adipose-derived mesenchymal stem cells (ADSCs) in the rapid progression of osteosarcoma is still unclear. Here, we found that ADSCs promoted tumour growth and invasion by increasing matrix metalloproteinase 2/9 (MMP2/9) expression in tumour cells. The persistent activation of signal transducer and activator of transcription 3 (STAT3) has been shown to directly promote tumour growth by mediating a wide spectrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 46 publications
(45 reference statements)
5
44
0
Order By: Relevance
“…Several studies have confirmed that mesenchymal stem cells promote the proliferation of osteosarcoma cells both in vitro and in vivo [38,[46][47][48][49]. Mesenchymal stem cells, the low differentiated precursor of various cell-types including osteoblast [16], in contrast to differentiated osteoblasts appear unable to communicate with osteosarcoma cells through the establishment of functional gap junctions [50].…”
Section: Mesenchymal Stem Cells Control Osteosarcoma Development: Potmentioning
confidence: 99%
“…Several studies have confirmed that mesenchymal stem cells promote the proliferation of osteosarcoma cells both in vitro and in vivo [38,[46][47][48][49]. Mesenchymal stem cells, the low differentiated precursor of various cell-types including osteoblast [16], in contrast to differentiated osteoblasts appear unable to communicate with osteosarcoma cells through the establishment of functional gap junctions [50].…”
Section: Mesenchymal Stem Cells Control Osteosarcoma Development: Potmentioning
confidence: 99%
“…Studies evaluating OS, a primary malignancy of bone that mostly affects children and young adults, have seen similar effects . Wang et al found that ASCs promote OS growth and metastasis through upregulation of MMP2 and MMP9 through STAT3 activation.…”
Section: Ascs In Cancermentioning
confidence: 91%
“…Wang et al found that ASCs promote OS growth and metastasis through upregulation of MMP2 and MMP9 through STAT3 activation. STAT3 inhibition attenuated these effects, decreased MMP2/9 expression, and prolonged survival in mice . Although the upstream activators of STAT3 were not identified, STAT3 is activated by many of the aforementioned paracrine factors from ASCs.…”
Section: Ascs In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al. found that adipose‐derived mesenchymal stem cells (ADSCs) promoted tumor growth and invasion in OS cells by increasing MMP2/9 expression through the activation of signal transducer and activator of transcription 3 (STAT3) pathways . Few studies reported that the expression of MMP‐2 in OS tissues is higher than in other tissues.…”
Section: Mmps Promote Osteosarcoma Progressionmentioning
confidence: 99%